G284(P) Where do the children play? A cross-sectional analysis of children's activities in rural gambia and their risk of diarrhoea. (May 2019) - Harris Snell, E; Cummins, C; Martin, JT; Holdsworth, W; Crowe, F; Sowe, J; Manjang, B; Manaseki-Holland, S
Abstract : Aims: Previous research has shown that young children from lower-income countries who play on soil contaminated with faecal bacteria may have an increased risk of diarrhoea. We describe the directly observed activities of young children in rural Gambia and assess whether exposure to the ground outside and factors such as who cares for the child are associated with the child's risk of diarrhoea. Methods: This was a cross-sectional analysis of secondary data from 735 randomly selected households with a child aged 6–36 months from 30 rural villages in The Gambia. Fieldworkers observed the children's activities and the presence of livestock in the compound, and caregivers reported diarrhoea in the children over the past week. The predictors of diarrhoea were assessed by using a mixed effects multivariate logistic regression model, adjusted for demographic, socio-economic and behavioural factors. Results: The majority (87.1%) of children were observed on the ground outside and 84.4% of children were in compounds that contained livestock. Some children (15.6%) were observed on the ground on multiple occasions but the longest period the children were observed on the ground was a median (IQR) of 93 (46–195) minutes. For every hour a child spent on the ground outside during the longest observed period, their risk of diarrhoea increased by 12.4% (adjusted OR=1.124, 95% CI=1.000–1.264, p=0.049). Having an older child, compared to an adult supervising the child reduced the risk of diarrhoea by nearly half (adjusted OR=0.523, 95% CI=0.344–0.794, p=0.002). Conclusion: This is the first study from rural Gambia to explore the activities of young children and quantify their exposure to soil on the ground and nearby livestock. The length of the longest period the child spent on the ground outside was positively associated with the risk of diarrhoea. This study highlights the need for interventions that will reduce young children's exposure to contaminated soil in compounds and suggests that older children as carers could play a part.